Evaluating the Anchorflow Suture Technique Versus Conventional Continuous Suturing in Vaginal Cuff Closure During TLH: A Multicenter Retrospective Analysis - Gizem Berfin Uluutku Bulutlar; Gizem Boz İzceyhan; Eralp Bulutlar; Fisun Vural (Medicina)
Background and Objectives: Total laparoscopic hysterectomy (TLH) is a commonly performed gynecological procedure. Vaginal cuff closure significantly impacts operative time and outcomes. This study evaluates the newly developed Anchorflow Suture (AFS) technique compared to conventional continuous suturing in terms of efficiency and safety. Materials and Methods: A multicenter retrospective cohort study was conducted at two tertiary referral hospitals involving 208 women who underwent TLH for benign indications. Women were divided into two groups based on vaginal cuff closure technique: AFS and continuous suturing. Demographic characteristics, surgical parameters, and postoperative outcomes were analyzed using appropriate statistical tests, with a significance level of p < 0.05. Results: No significant differences were found between groups in age, BMI (body mass index), gravida, parity, or menopausal status. Vaginal cuff closure time was significantly shorter with AFS (10.26 ± 2.3 min) compared to continuous suturing (13.36 ± 2.8 min, p < 0.001). Operative time was shorter in the AFS group, though not statistically significant (p = 0.15). Both techniques demonstrated similar safety profiles, with no cases of vaginal cuff dehiscence and comparable rates of granulation tissue formation, bleeding, and urinary incontinence. The AFS group showed a slightly lower incidence of postoperative bleeding (five cases vs. three cases). Conclusions: The AFS technique significantly reduces vaginal cuff closure time and demonstrates a comparable safety profile to continuous suturing. This method enhances surgical efficiency without increasing complications. Further prospective studies are needed to evaluate its long-term effects on pelvic floor integrity, sexual function, and surgeon proficiency.